Oocyte-targeted deletion reveals that hsp90b1 is needed for the completion of first mitosis in mouse zygotes. - Christophe Audouard; Florent Le Masson; Colette Charry; Zihai Li; Elisabeth S Christians (PLoS ONE, 2011)
Hsp90b1 is an endoplasmic reticulum (ER) chaperone (also named Grp94, ERp99, gp96,Targ2, Tra-1, Tra1, Hspc4) (MGI:98817) contributing with Hspa5 (also named Grp78, BIP) (MGI:95835) to protein folding in ER compartment. Besides its high protein expression in mouse oocytes, little is known about Hsp90b1 during the transition from oocyte-to-embryo. Because the constitutive knockout of Hsp90b1 is responsible for peri-implantation embryonic lethality, it was not yet known whether Hsp90b1 is a functionally important maternal factor.To circumvent embryonic lethality, we established an oocyte-specific conditional knockout line taking advantage of the more recently created floxed Hsp90b1 line (Hsp90b1(flox), MGI:3700023) in combination with the transgenic mouse line expressing the cre recombinase under the control of zona pellucida 3 (ZP3) promoter (Zp3-cre, MGI:2176187). Altered expression of Hsp90b1 in growing oocytes provoked a limited, albeit significant reduction of the zona pellucida thickness but no obvious anomalies in follicular growth, meiotic maturation or fertilization. Interestingly, mutant zygotes obtained from oocytes lacking Hsp90b1 were unable to reach the 2-cell stage. They exhibited either a G2/M block or, more frequently an abnormal mitotic spindle leading to developmental arrest. Despite the fact that Hspa5 displayed a similar profile of expression as Hsp90b1, we found that HSPA5 and HSP90B1 did not fully colocalize in zygotes suggesting distinct function for the two chaperones. Consequently, even if HSPA5 was overexpressed in Hsp90b1 mutant embryos, it did not compensate for HSP90B1 deficiency. Finally, further characterization of ER compartment and cytoskeleton revealed a defective organization of the cytoplasmic region surrounding the mutant zygotic spindle.Our findings demonstrate that the maternal contribution of Hsp90b1 is critical for the development of murine zygotes. All together our data indicate that Hsp90b1 is involved in unique and specific aspects of the first mitosis, which brings together the maternal and paternal genomes on a single spindle.